A MODEL OF AN ONLINE READING COMPREHENSION SUMMATIVE TEST FOR COLLEGE STUDENTS - Sofa Sofa; Gunadi H Sulistyo (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2017)
ABSTRACT There is an emerging phenomenon in some universities including STKIP PGRI Jombang regarding a compelling need of a test that can replace the existing paper-and-pencil based reading comprehension test, which is conventional, impractical, and time consuming. To fulfill the need, a model of an online reading comprehension summative test was developed, involving a number of essential micro skills of reading. The design of the study was Educational Research and Development (R&D), involving 100 subjects in the try-out stage. The instruments used were interview guides and questionnaire. Based on the tryout analysis, the reliability was .779, in which thirty one items were categorized as valid items. For the ease of scoring and the balanced number of the indicators under interest, only 25 items were included in the model test. Based on the students’ questionnaire, more than 80% subjects responded positively. The final product of this research was a set of an online reading comprehension test kit that includes the blueprint, the test (in form of paper and screenshot of the online version), the answer key, and the instruction to access the online test. ABSTRAK Di beberapa universitas termasuk STKIP PGRI Jombang, muncul kebutuhan penting sebuah tes yang bisa menggantikan tes membaca berbasis paper-and-pencil sebelumnya yang konvensional, tidak praktis dan memakan banyak waktu. Untuk memenuhi kebutuhan tes yang bisa mengatasi masalah tersebut, dikembangkanlah sebuah model tes membaca sumatif online. Desain penelitian ini adalah penelitian pengembangan, yang melibatkan 100 subjek dalam tahap try-out. Instrumen yang digunakan adalah interview guide dan kuesioner. Berdasarkan analisis butir soal, nilai alpha atau reliabilititas adalah 0.779. 31 butir soal dikategorikan sebagai butir soal yang valid. Untuk kemudahan penilaian dan keseimbangan jumlah indikator yang diinginkan, hanya 25 butir soal yang digunakan dalam model tes. Berdasarkan kuesioner mahasiswa, lebih dari 80% subjek merespon secara positif. Produk akhir dari penelitian ini adalah satu set online reading comprehension test yang meliputi kisi-kisi, tes (dalam bentuk kertas dan screenshot versi online), kunci jawaban dan instruksi untuk mengakses tes online. How to Cite: Sofa., Sulistyo, G.H. (2017). A Model of an Online Reading Comprehension Summative Test for College Students. IJEE (Indonesian Journal of English Education), 4(2), 168-187. doi:10.15408/ijee.v4i2.8344